PENGARUH INOVASI PRODUK, KUALITAS PRODUK DAN KESESUAIAN HARGA TERHADAP LOYALITAS KONSUMEN PADA MAHASISWI PENGGUNA HAIR CARE MAKARIZO DI UNIVERSITAS HKBP NOMMENSEN MEDAN - Natalia E Sihombing; Counsita Octavia Gultom (LPPM Universitas HKBP Nommensen, 2022)
This study aims to determine the effect of product innovation, product quality and price conformity on consumer loyalty to students using Makarizo Hair Care at HKBP Nommensen University, Medan, either partially or simultaneously. The type of research used is a quantitative approach, with a sample of 95 respondents. The types of data used are primary data and secondary data. Data collection techniques using a questionnaire. The data analysis method used is an instrument test consisting of validity and reliability tests, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, multiple linear regression analysis test and hypothesis testing consisting of t-test, F-test and coefficient of determination (R2). The results showed that Product Innovation had a positive and significant effect on Consumer Loyalty, this was indicated by the value of tcount (3.723) > ttable (1.986) and a significant value of 0.000 <0.05. Product quality has a positive and significant effect on Consumer Loyalty, this is indicated by the value of tcount (3.579) > ttable (1.986) and a significant value of 0.001 <0.05. Price Conformity has a positive and significant effect on Consumer Loyalty, this is indicated by the value of tcount (4.091) > ttable (1.986) and a significant value of 0.000 <0.05. Simultaneously it was found that Product Innovation, Product Quality and Price Conformity had a positive and significant effect on Consumer Loyalty, this was indicated by the value of Fcount (15.155) > Ftable (3.10) and a significant value of 0.000 <0.05. The coefficient of determination is 0.333, meaning that the variable Consumer Loyalty can be explained by Product Innovation, Product Quality and Price Conformity, which can be explained by 33.3%. While the remaining 66.7% is explained by other variables not explained in this study. It is recommended that Makarizo product innovation and quality be improved but still pay attention to price suitability.